PENGARUH LINGKUNGAN YANG KOROSIF TERHADAP LAJU KOROSI PADA BAHAN BANGUNAN BERBAHAN DASAR BESI - Adyanto Prakoso; Markus Karamoy Umboh; Romels C A Lumintang (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
The goal of this research is on understanding the influence of corrosive environment on base metal and its corrosion rate at various metals using case example at Kanonang Hill as the locus. An experimental approach is taken to obtain a causal relationship to the rate of corrosion.Â  The result of the experiment showed that the influence of environment of Kanonang Hill is remarkable. The study also indicating various corrosion rate for various metals used in the experiments. The score of corrosion rate for Light Steel bolt material is at 10,22 mpy, Carbon Chanell 8.52, Mild Steel 22,87 mpy, Plain Iron Concrete 33.20 mpy, Plain Iron Concrete 33.20 mpy, plain iron concerete 33.20 mpy, cast iron castings 39.33 mpy and the last, the metal tiles reaching 2.51 mpy.Keywords: Corrosive Environment, Building Material, Corrosion Level, Corrosion Rate.